1993
DOI: 10.1136/bmj.306.6878.622
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality and atenolol treatment.

Abstract: hypertensive patients.' In this study nifedipine plus diuretic lowered blood pressure more effectively than propranolol plus diuretic, which has previously been shown to be effective in black hypertensive patients.2 Although comparisons of fixed doses of drugs have limitations, the doses of propranolol and nifedipine used were in the middle of their therapeutic ranges. Experience in Kenyan hypertension clinics confirms reports that black hypertensive patients have lower plasma renin activities than white patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 4 publications
0
12
2
Order By: Relevance
“…This finding stands in contrast to an Australian case-control study reporting a significant 2-fold excess of renal pelvis cancer among women using nondiuretic antihypertensive drugs, especially beta-blockers (McCredie and Stewart, 1992). In addition, an excess of renal cancer has been suggested in 2 prospective surveys (Fletcher et al, 1993;Hole et al, 1993) of hypertensive patients taking beta-blockers, but the subsites were not specified and the relation was attributed to hypertension rather than medication use. Reasons for the differences are not clear, but the negative findings in our study may be Since the use of diuretics, beta-blockers and other antihypertensive drugs is highly correlated with hypertension, it is difficult to differentiate the effects of hypertension and its treatment on cancer risk.…”
Section: Discussioncontrasting
confidence: 79%
“…This finding stands in contrast to an Australian case-control study reporting a significant 2-fold excess of renal pelvis cancer among women using nondiuretic antihypertensive drugs, especially beta-blockers (McCredie and Stewart, 1992). In addition, an excess of renal cancer has been suggested in 2 prospective surveys (Fletcher et al, 1993;Hole et al, 1993) of hypertensive patients taking beta-blockers, but the subsites were not specified and the relation was attributed to hypertension rather than medication use. Reasons for the differences are not clear, but the negative findings in our study may be Since the use of diuretics, beta-blockers and other antihypertensive drugs is highly correlated with hypertension, it is difficult to differentiate the effects of hypertension and its treatment on cancer risk.…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast to the above observations, one longitudinal and three case-controlled studies found no association between use of β-blockers and malignancy [14,[55][56][57]. In one of the studies [14], the incidence rate of renal cell carcinoma was increased in those receiving β-blockers, although this could have been related to additional diuretic use in the same patients [58].…”
Section: β-Blockerscontrasting
confidence: 50%
“…This is consistent with our previous finding of a normal cancer mortality with atenolol treatment where the RR of methyldopa compared with atenolol was 1.5 in men (95% CI 1.0 to 2.2). 40 This excess cancer mortality occurred in earlier years of the study and may reflect confounding variables not fully accounted for by adjusting for the year of presentation and age.…”
Section: Discussionmentioning
confidence: 94%